Development of Karst Environment-Based Teaching Modules to Improve Learning Outcomes in Terms of Learning Motivation - Sitti Magfirah Ramadhana M; Pariabti Palloan; Abdul Haris (Postgraduate, University of Mataram, 2026)
This Research and Development (R&D) study aims to develop a Physics Teaching Module based on the Karst Environment using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) and evaluate its effectiveness on learning outcomes regarding student motivation. Content validity was assessed by two experts, while practicality was tested by a physics teacher. The module was trialed with 36 students in class XI F2 at SMAN 4 Maros. Data collection instruments included validation sheets, practitioner questionnaires, motivation scales, and learning achievement tests (pretest and posttest). Data analysis techniques involved the Aiken’s V index for validity, descriptive statistics, the Paired Sample T-Test for effectiveness, and a One-Way ANOVA to analyze learning improvements based on motivation levels. Results indicate that the module is valid with an average Aiken’s V index of 0.81 and is categorized as practical based on practitioner responses of 82.20%. Furthermore, the module proved effective in improving learning outcomes, as evidenced by a significant difference between pretest and posttest scores (Sig. 0.00 < 0.05), with significant differences also observed among students with varying levels of motivation (Sig. 0.00 < 0.05). In conclusion, this Karst environment-based physics module is declared valid, practical, and effective for use in school physics learning processes